ANALYSIS OF THE CULTURIZATION OF AHORRO IN NIÑOS OF THE PRIMER CICLO IN THE E.E.B. - Beatriz Sosa Pereira, Cecilia; Belen Sanabria Meira, Milena; Angélica Genez Arzamendia, Rocío; Beatriz Vázquez, Vanessa; Beatriz Arzamendia Gomez, Selva; Bella Martínez Flecha, Ana (Revista Gênero e Interdisciplinaridade, 2025)
Most financial problems are due to poor income management rather than actual income. Therefore, this research project emphasizes the importance of instilling financial literacy in children in their first cycle of high school. Finances are a part of every person’s life, from birth to death and beyond. Therefore, the sooner someone learns to manage them, the better. This research focuses on providing financial education to children in their first cycle and guiding parents on how to do so. It is divided into five main chapters. The first chapter presents the problem statement, questions, objectives, and justification for this research. Chapter two emphasizes the importance of teaching financial education, starting with basic concepts and analyzing the current situation in the country where the project is being developed. Chapter three then presents the research methodology. Chapter four provides an explanation and interpretation of the results obtained from the survey, as well as an account of the interviews conducted with the children. Finally, chapter five presents conclusions and proposals, which reflect the authors’ position on this topic.